Teenage sexuality, pregnancy, and childbearing - Furstenberg, Frank F., 1940-; Lincoln, Richard (Writer on pregnancy); Menken, Jane, 1939- (University of Pennsylvania Press, 1981)
Examining the social consequences of teenage childbearing, the editors explain the effects on adolescent parents themselves, their offspring, and their families, and discuss ways of preventing or tempering those effects. Why have Americans suddenly become troubled about teenage sexuality, pregnancy, and childbearing? These are not new problems, certainly, and the birthrate among teenagers--even the youngest of them--has been declining for some years. What has aroused public concern, according to the editors of these essays, is the increased visibility of the problem. The pregnant teenager is no longer expelled from school and forced to marry or discreetly bear a child out of wedlock. She has the option of abortion, and even if she decides to have the child, she is even more likely not to marry. Thus, the sensitivity of Americans to the issues of abortion and illegitimacy is inexorably linked to their concern about adolescent sexuality and pregnancy. The attention focused on the problem has resulted in a considerable amount of research on the causes and consequences of teenage pregnancy, and on the means of preventing it. Over the past decade, Family Planning Perspectives has published much, if not most, of the research on the causes, consequences, and means of coping with problems associated with teenage pregnancy and childbearing. From about 100 articles, the editors have selected 28 key reports that illuminate the issue for scholars, students, and professionals who work with young people in various settings. The contributors to the first section examine historical trends in regard to teenage sexual activity, use of contraception and abortion, pregnancy, and childbirth in and out of wedlock in the context of other changes in social structure and mores. The second section assesses the serious adverse consequences of early childbearing on the young people involved, on their children, and on society. The third section looks into what courses of action are practicable to help teenagers avert the pregnancies and births they do not wish to have, and to cope with problems resulting from early childbearing. The final section evaluates current programs and materials designed to help teenagers prevent unwanted pregnancies or deal with pregnancy when it occurs; it also reviews the state of the law involving contraception, abortion, and pregnancy among teenagers. The book includes an overview and section introductions by the editors, which draw together the implications of the contributions and those of other investigators who have written on this subject. All articles, as well as the editors' contributions, are followed by extensive, up-to-date bibliographies.